Oral Myiasis Affecting Gingiva in a Child Patient: An Uncommon Case Report - Fareedi Mukram Ali; Kishor Patil; Sanjay Kar; Atulkumar A. Patil; Shabeer Ahamed (Hindawi Limited, 2016)
Certain dipteran flies larvae causing invasion of the tissues and organs of the humans or other vertebrates are called as myiasis, which feed on hosts dead or living tissues. It is well documented in the skin and hot climate regions; underdeveloped countries are affected more commonly. Oral cavity is affected rarely and it can be secondary to serious medical conditions. Poor oral hygiene, alcoholism, senility, or suppurating lesions can be associated with the oral myiasis. Inflammatory and allergic reactions are the commonest clinical manifestations of the disease. In the present case, gingiva of maxillary anterior region was affected by larval infection in a 13-year-old mentally retarded patient.